KESANTUNAN BERBAHASA SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS VIII SMPN 20 KOTA KUPANG - Bukangtonung, Mariam; Djawa, Alex; Nitbani, Semuel H (Jurnal Lazuardi, 2025)
A qualitative descriptive study conducted at SMPN 20 Kota Kupang aimed to describe, depict, explain, and provide a more detailed answer to the research problem by studying an individual, group, or event as thoroughly as possible. According to Leech, the principles of politeness in language include the maxim of tact, maxim of simplicity, maxim of agreement, maxim of appreciation, and maxim of sympathy. The researcher found 10 data containing 5 forms of compliance with the principles of politeness in language among teachers and students in Indonesian language learning, consisting of 2 data on the maxim of tact, 1 data on the maxim of simplicity, 2 data on the maxim of agreement, 3 data on the maxim of appreciation, and 1 data on the maxim of sympathy. Furthermore, the researcher found data containing 5 forms of violation of the principles of politeness in language among teachers and students in Indonesian language learning, consisting of 4 types of maxims, namely 1 data on the maxim of tact, 2 data on the maxim of appreciation, and 1 data on the maxim of agreement.